Evaluating the Translation of Islamic Terminologies in Islam: The Faith of Love and Happiness - Pratiwi, Yulya Era; Syahriyani, Alfi (UIN Syarif Hidayatullah Jakarta, 2022)
This research aims to identify the translation procedure and translation quality of the book Islam: Risalah Cinta dan Kebahagiaan, written by Haidar Bagir and its English translation version Islam: The Faith of Love and Happiness, translated by Sayed Hyder. It employed qualitative descriptive method to describe the data. The collected data was categorized based on the terms associated with ibadah (worshiping) and muamalah (dealing). It was obtained by carefully reading the books both in the source and the target language, and analyzed using Newmark's translation procedure (1988) and Nababan’s translation quality (2012). This research found 23 data categorized as worshiping terms and 13 data categorized as dealing terms. The results showed that there were 9 translation procedures employed by the translator, where couplet contributed to create a high accuracy level, while synonymy created the low accuracy level. It also revealed that synonymy procedure created a high acceptability level whereas naturalization procedure showed the low acceptability level.